Innovation of Web-Based Digital Attendance System with Double Validation for Student Attendance Authentication via QR Code, Selfie, and Geolocation (Case Study: SMK Negeri 1 Bojonegoro): Inovasi Sistem Kehadiran Digital Berbasis Web dengan Validasi Ganda untuk Verifikasi Kehadiran Siswa Melalui Kode QR, Foto Diri, dan Geolokasi (Studi Kasus: SMK Negeri 1 Bojonegoro) - Muhammad Rinov Cuhanazriansyah; Ahmad Kholiqul Amin; Aprilia Eka Widiana (Universitas Putra Indonesia YPTK Padang, 2026)
This study aims to develop a web-based digital attendance system with dual validation using QR Code, selfie verification, and geolocation to improve the accuracy, efficiency, and transparency of student attendance recording at SMK Negeri 1 Bojonegoro. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The trial subjects included 35 students, 1 teacher, and 1 school operator. Data were collected through observation, interviews, documentation, and questionnaires. The system quality was evaluated using the ISO/IEC 9126 standard, which includes functionality, reliability, usability, efficiency, and maintainability, while user satisfaction was measured using a Likert scale. The results showed that the system was successfully developed and could be used according to the school's needs. The system quality test obtained an average score of 4.1 (good category), while the user satisfaction level achieved an average score of 3.9 (good category). The system is considered capable of simplifying the attendance process, accelerating access to attendance data, reducing the potential for attendance fraud, and supporting real-time attendance monitoring. Therefore, this web-based digital attendance system is feasible to be used as a more effective attendance solution in the school environment.